2023
DOI: 10.3390/foods12203878
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Microalgae in Foods, Pharma and Feeds and Their Use as Fertilizers and Biostimulants: Legislation and Regulatory Aspects for Consideration

Min Su,
Leen Bastiaens,
Joran Verspreet
et al.

Abstract: Microalgae are a rich resource of lipids, proteins, carbohydrates and pigments with nutritional and health benefits. They increasingly find use as ingredients in functional foods and feeds as well as in cosmetics and agricultural products including biostimulants. One of their distinct advantages is their ability to grow on wastewaters and other waste streams, and they are considered an environmentally friendly and cheap method to recover nutrients and remove pollutants from the environment. However, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 164 publications
0
7
0
Order By: Relevance
“…could remove 99% of ammonia, 92% of chemical oxygen demand (COD), and 100% of phosphorus. In this case, the microalgal biomass was oriented towards the production of biodiesel of high quality (Su et al, 2023). This study showed that D14 can grow on piggery wastewater up to 20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…could remove 99% of ammonia, 92% of chemical oxygen demand (COD), and 100% of phosphorus. In this case, the microalgal biomass was oriented towards the production of biodiesel of high quality (Su et al, 2023). This study showed that D14 can grow on piggery wastewater up to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of biofertilizers and biostimulants as a natural product is particularly crucial to avoid the use of chemicals that may lead to environmental contamination, namely in soil, water and affect the quality of the food produced. Numerous efforts are being made to expand the application of these natural biostimulants (Navarro-López et al, 2020; González-Pérez et al, 2021; Sánchez-Quintero et al, 2023) under strict legislations and regulations that depends on the continent (Su et al, 2023). The use of microalgae as biostimulants has acquired importance for their role in the sustainability and circular bieconomy agenda (Ajeng et al, 2022; Sánchez-Quintero et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…They play essential roles in photosynthesis and protect cells from damage by absorbing blue light and acting as antioxidants. The interest in these compounds has grown significantly due to their potential in various sectors [ 72 , 73 , 74 , 75 ]. Sampathkumar and Gothandam studied the effect of sodium bicarbonate on lutein biosynthesis in Chlorella pyrenoidosa , highlighting the influence of environmental conditions on lutein production in green microalgae [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, it holds second place in (health) beverage production. Proteins of the nutrient-rich D. salina are also used in the baking industry [36,43].…”
Section: Arthrospira and Dunaliella Are Among The Most Commercially A...mentioning
confidence: 99%